Prenatal ultrasound diagnosis of anterior abdominal wall defects in sub Saharan Africa; simple but often missed - Shitta, Andrew H.; Isichei, Mercy W.; Dung, Ezekiel D.; Peter, Solomon D.; Ode, Michael B.; Jatau, Isaac A.; Ottah, Onyedikachi N.; Ale, Alexander F. (International Journal of Research in Medical Sciences, 2021)
Background: Congenital anterior abdominal wall defects (AAWD) is a spectrum of abdominal wall defects that includes omphalocele, gastroschisis, bladder exstrophy, cloacal exstrophy, prune belly syndrome and pentalogy of Cantrell. Early Prenatal diagnosis of AAWD provides opportunity for abnormal karyotypes screening and planned delivery in a specialized centre. Ultrasound can detect these defects during pregnancy. This study aims to evaluate the detection rate of AAWD during routine obstetric ultrasonography in our region. Methods: A retrospective study of all patients that presented with AAWD to our centre from January 2008 to July 2020. Data included patient’s age, sex, birth weight, diagnosis, resuscitation time, outcome, maternal age, parity and antenatal ultrasound scan (USS) records. Antenatal USS before 12 weeks only, were excluded. Data analysed using excel. Results: Of the 140 with AAWD, 84.29% had omphalocele, 10% gastroschisis, 2.14% prune belly syndrome and 0.71% each with bladder exstrophy, cloacal exstrophy and pentalogy of Cantrell. There were 123 booked pregnancies. Majority (112) had antenatal care elsewhere while 11 attended our Centre. Ultrasonography of 108 pregnancies scanned at12 weeks or beyond, had 4 confirmed prenatal diagnosis of AAWD. All done in our centre. Mean gestational age at diagnosis was 24weeks. Outcome was rupture1 (25%) and 25% mortality (prenatally diagnosed) and 51.92% mortality for patients with missed diagnosis. Conclusions: Our obstetric ultrasound detection rate of AAWD is very low. There is a need for improvement in training to improve perinatal care of these defects.